Two-dimensional strain field data from Distributed Optical Fibre Sensors in a wall element - Strain data from distributed optic fibre sensors of a wall element loaded under three-point test - Fernandez, Ignasi (Chalmers University of Technology, 2023)
The data available provides information of the strain fields in a wall element under loading. The data describes strains in three direction of the mid-plane section of the wall. The data was retrieved during the testing of the wall element in a three point test configuration. The information about the applied load is as well included in the data set.

The data included in this dataset basically consists in strain measurement of fibre optic sensor, i.e. BRUSens V9 cables, deployed in a multi-layer configuration at the mid-section of a wall element. The equipment to measure the strains from the sensors is an ODISI 6004 from Luna ink. which uses the Rayleight backscatter technology.
The dataset is available in MatLab and JSON file formats.

Tillgängliga data ger information om töjningsfälten i ett väggelement under belastning. Data beskriver töjningar i tre riktningar av väggens mittplanssektion. Data hämtades under testningen av väggelementet i en trepunktstestkonfiguration. Informationen om den applicerade belastningen ingår också i datamängden.

Data som ingår i denna datauppsättning består i grunden av töjningsmätning av fiberoptisk sensor, d.v.s. BRUSens V9-kablar, utplacerade i en flerskiktskonfiguration i mittsektionen av ett väggelement. Utrustningen för att mäta spänningarna från sensorerna är en ODISI 6004 från Luna ink. som använder Rayleights backscatter-teknik.
Datauppsättningen är tillgänglig i formaten MatLab och JSON fil.
Tvådimensionell töjningsfältdata från distribuerade optiska fibersensorer i ett väggelement - Töjningsdata från distribuerade optiska fibersensorer för ett väggelement laddat under trepunktstest
Keywords: wall element; väggelement; principal strains; huvudtöjningar; d-region; d-region; distributed optic fibre sensing; distribuerad fiberoptisk mätning; Engineering and Technology; Teknik; Civil Engineering; Samhällsbyggnadsteknik; Other Civil Engineering; Annan samhällsbyggnadsteknik